Pengaruh Kepemilikan Manajerial, Proporsi Dewan Komisaris, Independensi - Idzal Dwi Nantyah; Nisful Laila (Universitas Airlangga, 2017)
The aim of this study was to determine the effect of good corporate governance,growth of sales, and firm size on ROE of BUMN firm that listed ISSI Period 2011-2014. The method used is quantitative method with panel data regression techniques. The data used is secondary data by collecting data annual financial statements of BUMN firms that listed in ISSI period 2011-2014. Panel data regression conducted showed that managerial ownership (X1) negative and significant impact on ROE, the proportion of commissioners positive and significant impact on ROE (X2), the independence of audit committee (X3) negative and significant impact on ROE, growth of sales (X4) positive and significant impact on ROE, firm size (X5) positive and significant impact on ROE as well as managerial ownership, the proportion of commissioners, the independence of audit committee, growth of sales, and firm size simultaneously affect ROE of BUMN firms period 2011-2014.